Establishing the Predictive Validity of the Assessment of Motor and Process Skills for Driving Performance Outcomes. - Dickerson, Anne E.; Wu, Qiang; Houston, Helen; Cassidy, Therese; Touchinsky, Susan (American Journal of Occupational Therapy)
Importance: Although the Assessment of Motor and Process Skills (AMPS) is an excellent tool for evaluating the functional performance of instrumental activities of daily living (IADLs), a limited number of studies have used the AMPS for decisions regarding the IADL of fitness to drive and community mobility. Objective: To determine the specificity and sensitivity of the AMPS as a tool for determining a person's fitness to drive. Design: Cross-sectional observational design. Setting: Three driving rehabilitation programs in three states. Participants: Participants were 388 community-living adults (M age = 68.74 yr, SD = 11.53); 196 adults were recruited before completing a comprehensive driving evaluation, and 192 were recruited in two other studies of older drivers. Outcome and Measures: AMPS and results of comprehensive driving evaluation or on-road assessment. Results: Using a logistical regression, AMPS Motor and Process Skills scores yielded a sensitivity of 84.6% and a specificity of 88.8%. The odds ratio of the AMPS Motor Skills score was.347; for the AMPS Process Skills score, it was.014. Using cross-validations, the model with AMPS Motor and Process scores produced a cross-validation area under the curve of.918, with sensitivity and specificity of 84.6% and 88.4%, respectively, and a probability greater than.334 was used for predicting a fail or drive-with-restriction evaluation. Conclusions and Relevance: The AMPS Motor and Process Skills scores revealed significant differences between those who failed or had driving restrictions and with those who passed the driving evaluation, which supported the AMPS as an effective tool for predicting fitness to drive. Plain-Language Summary: This study demonstrates how the Assessment of Motor and Process Skills (AMPS), as a top-down occupational therapy assessment tool, can be used to differentiate between medically at-risk drivers who are likely to pass a comprehensive driving evaluation and those who are likely to fail or need restrictions. AMPS will assist occupational therapy practitioners in determining who is most appropriate to receive driving rehabilitation services and/or when to refer a person for a comprehensive driving evaluation. This study found that the Assessment of Motor and Process Skills (AMPS) can be used to differentiate between medically at-risk drivers who are likely to pass a comprehensive driving evaluation and those who are likely to fail or need restrictions.